Control of coal mine bursts - by K. Y. Haramy, J. P. McDonnell, and L. A. Beckett Technical Papers, MINING ENGINEERING, Vol. 40, No. 4 April 1988, pp. 263-267 - G. Bräuner (Society for Mining, Metallurgy & Exploration, 1990)
The methods of burst control treated in the authors' very informative paper have been applied in the Ruhr Coalfield, Germany, for more than 20 years and have proved to be highly effective. It might be interesting here to mention a few experiences: The symptoms of critical stresses when drilling with small diameters ("test drilling") are essentially the same as described. However, we consider the situation safe if these symptoms occur beyond a certain distance ahead of the face. That safety distance equals three times the seam thickness plus the daily advance. It is the total seam thickness that counts, not merely the mined portion. Critical stresses within the safety distance are dissolved by so-called destressing measures: drilling with heavier equipment, blasting, or water infusion. To avoid bump initiation, the destressing operations should begin at the sides of the stressed zone rather than in the middle. As to water injection, there are two different principles. If the situation is critical already, high pressures are applied for hydraulic fracturing. If the stresses still allow to drill deep holes, the fluid pressure is kept low and acts for a longer time. This is to make the coal break successively instead of violently - a long-term precaution. When the stresses are very high, destressing is the most appropriate means. We mostly drill with 95 mm-diam (3.7 in.- diam). The techniques in detail are somewhat complex and subject to modifications. But the general idea is to accomplish burst prevention by controlling the potential burst situations.